2019
DOI: 10.3390/molecules24112149
|View full text |Cite
|
Sign up to set email alerts
|

Improved Carotenoid Processing with Sustainable Solvents Utilizing Z-Isomerization-Induced Alteration in Physicochemical Properties: A Review and Future Directions

Abstract: Carotenoids—natural fat-soluble pigments—have attracted considerable attention because of their potential to prevent of various diseases, such as cancer and arteriosclerosis, and their strong antioxidant capacity. They have many geometric isomers due to the presence of numerous conjugated double bonds in the molecule. However, in plants, most carotenoids are present in the all-E-configuration. (all-E)-Carotenoids are characterized by high crystallinity as well as low solubility in safe and sustainable solvents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 134 publications
(223 reference statements)
1
70
0
Order By: Relevance
“…This mechanism of action is further highlighted in our experiments by partial or non-degradation of fucoxanthin in MeOH/DCM extracts which is the only xanthophyll 5,6-epoxide to have its position eight occupied by a ketone group that blocks rearrangement to a 5,8-dihydrofuran ring. In this case, the epoxide isomerization results in a partial isomerization of fucoxanthin into cis-fucoxanthin which is not observed when carotenoids analyses are performed on fresh acetone extracts [61,62].…”
Section: Carotenoidsmentioning
confidence: 97%
See 1 more Smart Citation
“…This mechanism of action is further highlighted in our experiments by partial or non-degradation of fucoxanthin in MeOH/DCM extracts which is the only xanthophyll 5,6-epoxide to have its position eight occupied by a ketone group that blocks rearrangement to a 5,8-dihydrofuran ring. In this case, the epoxide isomerization results in a partial isomerization of fucoxanthin into cis-fucoxanthin which is not observed when carotenoids analyses are performed on fresh acetone extracts [61,62].…”
Section: Carotenoidsmentioning
confidence: 97%
“…Mar. Drugs 2020, 18, 122 6 of 18 results in a partial isomerization of fucoxanthin into cis-fucoxanthin which is not observed when carotenoids analyses are performed on fresh acetone extracts [61,62].…”
Section: Carotenoidsmentioning
confidence: 99%
“…Namely, several studies have indicated that Z ‐isomers of carotenoids such as lycopene and astaxanthin have higher bioavailability and antioxidant activity than the all‐ E ‐isomers. [ 14–17 ] In addition, Z ‐isomers of astaxanthin and fucoxanthin potentially have higher anti‐inflammatory activity and anticancer activity, respectively, than their all‐ E ‐isomers. [ 18,19 ] Thus, in some cases, the intake of Z ‐isomers of carotenoids, rather than all‐ E ‐isomers, is preferable for human health, and the development of Z ‐isomer‐rich carotenoid products such as supplements is expected.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when adonirubin, astaxanthin, and adonixanthin are used for the above applications, it is desirable that their Z ‐isomer (Figure 1d,e) contents are high. [ 14–18 ] However, there have been no reports on the storage stability of the xanthophyll isomers against heating and photo‐irradiation. Therefore, the objectives of this study were to investigate the effect of thermal treatment and photo‐irradiation on the stability of adonirubin, astaxanthin, and adonixanthin having high Z ‐isomer content in comparison with the all‐ E ‐isomers in a model system.…”
Section: Introductionmentioning
confidence: 99%
“…(all‐ E )‐Carotenoids, including lycopene, are relatively easily isomerized to the Z ‐isomers by heating, light irradiation, and addition of Z ‐isomerization‐accelerating catalysts such as iron(III) chloride and polysulfides . However, to promote the Z ‐isomerization reaction by these methods, it is necessary to dissolve carotenoids in media such as organic chemicals . In recent years, consumers have increasingly demanded discontinuation of the use of these chemicals in food processing.…”
Section: Introductionmentioning
confidence: 99%